Hubungan Usia Dan Tingkat Pendidikan Ibu Hamil Terhadap Kepatuhan Kunjungan Antenatal Care Di Puskesmas Muara Pinang Kabupaten Empat Lawang Tahun 2023 - Kharisma Delta Sari; Murwati Murwati; Desi Aulia Umami (Universitas Dehasen Bengkulu, 2023)
Antenatal care is a service provided by health workers to women during pregnancy, for example by monitoring physical, psychological health, including fetal growth and development and preparing for labor and birth so that the mother is ready to face a new role as a parent (Wagio & Putrono, 2016). The purpose of the study was to find out the relationship between age and education level of pregnant women on compliance with antenatal care visits at the Muara Pinang Health Center, Empat Lawang Regency in 2023. This type of research is analytic research using this type of research is analytic research using a cross-sectional design (Hidayat, 2012). The population of this study were all pregnant women from trisemester 1-3 in the working area of the muara pinang health center, four lawang district in 2022, totaling 75 people. the number of samples in this study were 43 respondents. The results of this study indicate that almost half of the respondents 20 (46.5%) were 20-35 years old, almost half of the respondents 18 (41.9%) had secondary education, more than half of the respondents 25 (58.1%) were compliant with ANC visits, There is a relationship between the age of pregnant women and compliance wi There is a relationship between the education of pregnant women and the compliance of antenatal care visits at the Muara Pinang Health Center, Empat Lawang Regency in 2023 Suggested results of this study To the health center To the health center to prioritize patient services, especially making efforts to improve health services related to the competence of nurses martenitas with accuracy in providing health care to pregnant women.th antenatal care visits at the Muara Pinang Health Center, Empat Lawang Regency in 2023,